Evaluation of Cytotoxicity and Biocompatibility of Ti2AlC in Rabbits - Ibrahim , Luma M; Jassim , Raghdaa K; Al Gabban, Ahmed (Journal of Baghdad College of Dentistry, 2021)
Background: The Titanium and its alloys are suitable for dental implant and medical applications. Biocompatibility of the materials is a major factor in determining the success of the implant and has a great impact on their rate of osseointegration. The aim of this study was to evaluate the biocompatibility and cytotoxicity of Ti2AlC in comparison to CPTi & Ti6Al7Nb in rabbits. Materials and Methods: 10 male New Zealand White rabbits, weighing (2-2.5 kg), aged (10-12 months) were used in this study. Cylindrical implants were prepared from the study materials (CPTi, Ti6Al7Nb and Ti2AlC) with (8mm) height and (3mm) diameter for the evaluation of tissue response and disc specimens were prepared with (6 mm) diameter and (2 mm) thickness for evaluation of cytotoxicity MTT test. A histological study was performed at 2 & 6 weeks post- surgical implant insertion.Results: Histological findings show that Ti2AlC has enhanced proliferation of osteo-progenitor cell and reported mature bone formation at 6 weeks. Moreover, Ti2AlC has recorded a higher percentage for viable cells by MTT test in comparison to CPTi and Ti6Al7Nb.Conclusion: The new Ti2AlC dental implant is considered biocompatible and has showed a better bone formation than the CPTi and Ti6Al7Nb materials at 2 & 6 weeks.